Handedness differences in eye-hand coordination and, choices, simple reaction time of international handball players - Awamleh, A. A.; Mansi, T.; Akhaldi, H. (Journal of Physical Education and Sport, 2013)
The purpose of this study was to observe handedness differences between Jordanian women's international handball team in cognitive task performance (eye hand coordination, Choices, simple reaction time and movement times). Twelve females nine right handed (based on hand used for writing) and 3 left handed, aged 17 to 25 years (M = 21,3 yr, SD = 2,7) participated in this study . Measurements for reaction time were taken using the Reaction Time Apparatus Lafayette Instrument Multi Operational Apparatus for Reaction Time Model 35600 and eye hand coordination by Steadiness Tester, Hole Type Model 32011. The result indicated that there were significant differences found between right handed and left-handed in terms of simple Auditory Reaction time high tone, and visual choice reaction time movement time.